Pengaruh Pendidikan dan Pelatihan terhadap Kinerja Pegawai: Kajian 5 Jurnal Internasional Pendidikan dan Pelatihan Sumber Daya Manusia - Zahra, Indria Ikhtia; Damayanti, Mahfirar Ryani; Abidin, Muhammad Nur; Ritonga, Moh. Iqbal Prasetyo (As-Syirkah: Islamic Economic & Financial Journal, 2024)
The purpose of writing this journal is to analyze and compare the five international journals that discuss Human Resources Education and Training. The theme raised was regarding the influence of education and training on employee performance. The research method used is qualitative with library study data collection techniques. The results of the analysis prove that the existence of HR education and training in the world of work greatly influences employee performance, therefore companies should be more open to training and education.